2002
DOI: 10.1046/j.1432-1033.2002.02916.x
|View full text |Cite
|
Sign up to set email alerts
|

A new high affinity binding site for suppressor of cytokine signaling‐3 on the erythropoietin receptor

Abstract: Erythropoietin (Epo) is a hematopoietic cytokine that is crucial for the differentiation and proliferation of erythroid progenitor cells. Epo acts on its target cells by inducing homodimerization of the erythropoietin receptor (EpoR), thereby triggering intracellular signaling cascades. The EpoR encompasses eight tyrosine motifs on its cytoplasmic tail that have been shown to recruit a number of regulatory proteins. Recently, the feedback inhibitor suppressor of cytokine signaling‐3 (SOCS‐3), also referred to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 52 publications
2
62
0
Order By: Relevance
“…However, many reports have shown that SOCS3 inhibits cytokine signaling by binding cytokine receptors at a putative immunoreceptor tyrosine-based inhibitory motif (ITIM). 11,13 Mutation of the EPOR ITIM reduces the inhibitor effect of SOCS3, suggesting that it interacts with both JAK2, probably via its kinase inhibitory region (KIR), and the EPOR. This may explain why SOCS3 blunts the EPO response so strongly and why SOCS1 does not enhance the JAK2 V617F response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, many reports have shown that SOCS3 inhibits cytokine signaling by binding cytokine receptors at a putative immunoreceptor tyrosine-based inhibitory motif (ITIM). 11,13 Mutation of the EPOR ITIM reduces the inhibitor effect of SOCS3, suggesting that it interacts with both JAK2, probably via its kinase inhibitory region (KIR), and the EPOR. This may explain why SOCS3 blunts the EPO response so strongly and why SOCS1 does not enhance the JAK2 V617F response.…”
Section: Discussionmentioning
confidence: 99%
“…Ba/F3-SOCS3 cells 11 were retrovirally infected with EPOR pMX-IRES-GFP, JAK2 V617F pMX-IRES-CD4, or JAK2 WT pMX-IRES-CD4. 2 293T cells were transfected with 2 g SOCS1 pME18S Flag, SOCS2 pME18S Flag, SOCS3 pME18S Flag, JAK2 WT pRK, and JAK2 V617F pRK as appropriate using FuGENE (Roche Diagnostics, West Sussex, United Kingdom).…”
Section: Cells and Transfectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these modules contributes to attenuation of the duration and intensity of JAK-STAT signalling. The SH2 domain is responsible for SOCS3 binding to both the phosphotyrosine residues within cytoplasmic domain of the receptor and JAK kinase following cytokine-mediated activation (Dunn et al 2005;Hortner et al 2002a;Hortner et al 2002b;Nicholson et al 2000;Sasaki et al 1999). As a consequence, SOCS3 is thought to inhibit signal transduction by directly inhibiting JAK activity through the kinase inhibitory region (KIR) located in the SOCS3 N-terminus .…”
Section: Introductionmentioning
confidence: 99%
“…Cytokine-inducible SH2-containing protein (CIS) interacts with phosphorylated Tyr-401 in EpoR and suppressor of cytokine signaling 3 (SOCS3) with phosphorylated Tyr-429 and Tyr-431 in addition to Tyr-401. CIS and SOCS3 both act as negative regulators of Epo signaling by inhibiting the activation of the STAT5 and ERK pathways (15)(16)(17). Furthermore, SH2 domain-containing tyrosine phosphatase 1 (SHP1) has been shown to associate with EpoR at Tyr-429 and Tyr-431.…”
mentioning
confidence: 99%